2015
DOI: 10.1007/s13361-015-1202-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Some Liquid Matrixes for Analyte Quantification by MALDI

Abstract: Abstract. Sample inhomogeneity is one of the obstacles preventing the generation of reproducible mass spectra by MALDI and to their use for the purpose of analyte quantification. As a potential solution to this problem, we investigated MALDI with some liquid matrixes prepared by nonstoichiometric mixing of acids and bases. Out of 27 combinations of acids and bases, liquid matrixes could be produced from seven. When the overall spectral features were considered, two liquid matrixes using α-cyano-4-hydroxycinnam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…It has been our experience that the calibration curve determined by our method for a given combination of analyte, matrix and instrument remains valid even a few years after its construction . The calibration curve shown above is essentially the same as the one reported previously . The calibration curve for imipramine (structure shown in the Fig.…”
Section: Resultsmentioning
confidence: 58%
See 4 more Smart Citations
“…It has been our experience that the calibration curve determined by our method for a given combination of analyte, matrix and instrument remains valid even a few years after its construction . The calibration curve shown above is essentially the same as the one reported previously . The calibration curve for imipramine (structure shown in the Fig.…”
Section: Resultsmentioning
confidence: 58%
“…Fournier et al demonstrated the imaging, although not quantitative, of lipids in cells by MALDI with ionic liquid matrixes . We reported that a genuinely fluidic liquid could be produced by the nonstoichiometric mixing of the above acids and bases and air‐drying of the mixture to eliminate the solvent—in profiling, a solution of liquid matrix in a solvent is loaded and dried . Such a liquid, which is not entirely ionic, remained fluidic, and hence homogeneous, even after prolonged storage inside a vacuum and after extensive bombardment—10 000 shots or more—by laser pulses .…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations